Laminar Viscous Fluid Flow with Micro-rotation Capabilities through Cylindrical Surface - Norasia, Yolanda; Tafrikan, Mohamad; Ghani, Mohammad (Universitas Muhammadiyah Mataram, 2022)
Viscous fluid can micro-rotate due to collisions between particles that affect viscous fluid's velocity and temperature.This study aims to determine the effect of viscosity parameters, micro-rotation materials, and heat sources on fluid velocity and temperature. The model of the laminar flow equation for viscous fluid in this study uses the laws of physics, namely, the law of conservation of mass, Newton II, and Thermodynamics I. The formed dimensional equations are converted into non-dimensional equations by using non-dimensional variables. Then, the non-dimensional equations are converted into similarity equations using stream function and similarity variables. The formed similarity equation was solved numerically by using the Gauss-Seidel method. The results of this study indicate that the velocity and temperature of the viscous fluid flow can be influenced by the parameters of viscosity, micro-rotation material, and heat source. The presence of collisions between particles causes heat to cause an increase in the variance of viscosity parameters, micro-rotation materials, and heat sources. Therefore, the viscous fluid's velocity decreases and its temperature increases.